Why public policy exceptions have not delivered and how to make them more effective - Catharine Titi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The interpretation of public policy exceptions is proving to be one of the biggest conundrums of international investment law and makes the application of international investment treaties unpredictable. This Perspective explains why public policy exceptions have not reached their full potential and provides guidance on making them more effective.
Keywords: 330